Photo-thermo-acoustic analysis of heterogeneous semiconductor structures under pulse laser irradiation - Burbelo, R.; Isaiev, M.; Kuzmich, A. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2011)
The analysis of photo-thermo-acoustic transformation in materials with the
modified properties of a surface layer has been made in this work. Formation of a photoacoustic
response in a layered structure of the type “implanted layer + crystalline Si
substrate” as a result of its irradiation by one laser pulse with duration of 20 ns is
analyzed.